New urban power grid flexible load dispatching architecture and key technologies - Zhang, Rui; Yu, Jilai (Frontiers in Energy Research, 2023)
Towards the dual-carbon goals, the new urban power grid (NUPG) dominated by new energy has a low proportion of adjustable power generation units, resulting in insufficient scheduling flexibility. As a result, it becomes challenging to cope with the complex operating conditions of the NUPG. In this paper, after analyzing the new operational characteristics and challenges of the NUPG, a flexible load dispatching architecture and key technologies for the NUPG are proposed. These enhance the scheduling flexibility of the NUPG from the load side, which further provides support for the operation of the large power grid. Then, the types of scheduling objects, scheduling methods, scheduling tasks, and four essential dispatching technologies are introduced to provide a reference for building the NUPG flexible load dispatching system. Finally, the effectiveness of the NUPG flexible dispatching architecture and technologies is verified by simulation analysis of the IEEE39-bus system and the actual power grid in East China.